2015
DOI: 10.1111/1754-9485.12408
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT diagnosis of non‐traumatic gastroduodenal perforation

Abstract: MDCT is useful in diagnosis of presence and site of GDP. Wall defect and/or ulcer and wall thickening have a high positive predictive value for localization of perforation site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
8
0
5
Order By: Relevance
“…As a result, many patients with unknown PUD present to emergency departments with unexplained acute abdomen and commonly undergo multidetector CT. Since perforated gastroduodenal ulcers represent the commonest cause of spontaneous pneumoperitoneum, suggesting the underlying presence of PUD is relatively straightforward when radiologists are faced with upper abdominal free air or peritonitis without CT signs of colonic diverticulitis and digestive tract masses [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many patients with unknown PUD present to emergency departments with unexplained acute abdomen and commonly undergo multidetector CT. Since perforated gastroduodenal ulcers represent the commonest cause of spontaneous pneumoperitoneum, suggesting the underlying presence of PUD is relatively straightforward when radiologists are faced with upper abdominal free air or peritonitis without CT signs of colonic diverticulitis and digestive tract masses [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that the sensitivity of US is superior to that of abdominal radiography for the diagnosis of pneumoperitoneum [5,63,65,73,96,97]. CT has the best overall sensitivity for the detection of free intraperitoneal gas [66,[98][99][100][101].…”
Section: Comparison Of Us With Other Imaging Methods and Diagnostic Smentioning
confidence: 99%
“…[89] Extraluminal air with predominant upper abdomen distribution around the stomach and liver is the most common (97%) CT finding, however, it may not be detected in cases of very small or contained perforation. [10] Gastric wall defect and/or ulcer is the second most common CT feature (84%) followed by extraluminal oral contrast (0–27%). [10] Other CT features include wall thickening, adjacent fat stranding, and fluid.…”
Section: Role Of Imagingmentioning
confidence: 99%
“…[10] Gastric wall defect and/or ulcer is the second most common CT feature (84%) followed by extraluminal oral contrast (0–27%). [10] Other CT features include wall thickening, adjacent fat stranding, and fluid.…”
Section: Role Of Imagingmentioning
confidence: 99%
See 1 more Smart Citation